Idol, or ideal? the Korean pop idol through critical phenomenology - Reyes, Joanna Ellina S.; Santos, Josefina C. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2018)
Abstract
In the present global media landscape, with the ubiquity of technology and communities growing past the physical, cultures converge and diverge to recreate the international, but nonetheless, local. Situated in the context of global phenomena comes the ever-present "celebrity" that has developed in societies all over the world to be a valuable multifaceted entity in itself. This has led to the emergence of the "idol", as such in case of Korean Pop music as a genre that has perpetuated through various locales, including the Philippines.

This research aims to define the K-Pop idol as a phenomenon. With the use of critical phenomenology along with the use of grounded theory departing from Richard Dyer's star theory, it examines methods, processes, and standards involved in the creation of the idol. With its analysis of mediated images and the context of South Korean values, it found that the idol is a celebrity or public individual that has been subjected to construction under an entertainment company and performs a role of performing music and images, while also being an entity reflective and negotiating of ideal and identities of audiences and fans that consume them.

Keywords: Hallyu, K-Pop, celebrity, idol, critical phenomenology, celebrification, star theory, grounded theory, cultural studies, production, fandom.
Abstrak
Sa kasalukuyang kaayusan ng midya, kung saan matutuklasan ang mga panibagong teknolohiya at pamayanan sa internet, mas madaliang nagbubukod-bukod at nagbubuklod-buklod ang kulturang pandaigdig at pansarili. Sa konteksto ng isang penomenon kung saan ang celebrity o artista ay mayroong nilulugaran sa bawat kultura, ang artistang ito ay siyang naging isang makabuluhang bahagi ng buhay na pang-araw-araw. Hango rito ang "idol", na isang malaking bahagi ng dyanrang pang-musiko na Korean Pop (K-Pop) at ng penomenon ng Korean Wave o Hallyu.

Ang layunin ng pananaliksik na ito ay bigyang depinisyon at kahulugan ang K-Pop idol bilang isang penomenon. Gamit ang kritikal na penomenolohiya at pagsaalang-alang sa star theory ni Richard Dyer, inaral nito ang iba't ibang mga paraan at pamantayan sa paggawa ng isang idol. Sa pag-aaral ng mga imahe't konseptong naibahagi sa midya, hango sa mga kultura ng kinauukulan ng K-Pop, nadatnan nito na ang idol ay isang artistang sumailalim sa pagbuo ng isang entertainment company, na mayroong tungkuling gumanap sa musika't mga imahe habang sinasalamin nito at nakikipag-ayos ito sa mga ideyal at pagkikilanlan ng mga manonood o indibidwadl na tumatangkilik sa kanya.

Keywords: Hallyu, K-Pop, celebrity, idol, critical phenomenology, celebrification, star theory, grounded theory, cultural studies, production, fandom.
Vita.
Keywords: Popular culture—Korean influences; Culture—Study and teaching; Celebrities